Comparative Study of Iron (III) Removal Using Charred Sugarcane Bagasse and Precipitating Agent Calcium Hydroxide - Homagai, Puspa Lal; Poudel, Sujan (Journal of Nepal Chemical Society, 2017)
Available with full text